Research on the judicial trend on the issues of perils, warranties, condition and duty of utmost good faith in fire insurance / Nuur Fakhizaa Abu Bakar, Siti Hadijah Ahmad and Nor Azila Maharam - Abu Bakar, Nuur Fakhizaa; Ahmad, Siti Hadijah; Maharam, Nor Azila (2006)
In competing our project paper, we have conducted a library research on various books and materials that are relate to our topics which are perils, warranties, condition and duty of utmost good faith. Furthermore, our research is also based on the judicial trend in fire insurance cases from the year 2000-2006. All the cases we find it in the online from the internet.